The Strength Performance of Polyurethane Cellular Foam (PUC) Block as Soil Improvement - ABD MAJID, USAID; Nik Normunira Mat Hassan; Chan Chee Ming; Nur Faezah Yahya (Progress in Engineering Application and Technology, 2025)
This study evaluates the effectiveness of Polyurethane Cellular Foam (PUC) blocks in enhancing the stability of road embankments on clay subgrades, which often face issues of low bearing capacity and high compressibility. PUC blocks were produced by mixing rigid polyurethane waste with flexible polyurethane in varying proportions (0%, 7.5%, 10%) under treated and untreated conditions. Compression tests (ASTM D3574-8) and unconfined compressive strength (UCS) tests (ASTM-D 2166) were conducted. Results showed that 7.5% treated PUC achieved the highest compressive strength (41.874 kPa) and Young’s modulus (10.07 kPa), while the highest UCS (25.00 kPa) was observed for 7.5% untreated PUC. Current geofoam materials face challenges such as low strength and deformation due to fluctuating stress, leading to structural failure (Srivastava et al., 2019). This study highlights the potential of PUC blocks to improve the stability of road embankments on clay subgrades.